Mortality attributable to housing deprivation in Belgium between 1991 and 2015. (20th October 2021) - Otavova, M; Faes, C; Masquelier, B; Devleesschauwer, B
Abstract: Background: Poor housing condition is associated with increased mortality. Our aim is to measure the inequality in mortality attributable to housing deprivation in Belgium. Methods: We utilized data on housing conditions from the 1991 population census, and data on mortality from the National Register in Belgium between Jan 1, 1991 and Dec 31, 2015. An area-level composite score was developed and computed for 18 267 statistical sectors in Belgium. The score was based on indicators encompassing multiple dimensions: occupancy status and its density, absence of central heating, bathroom, toilet, kitchen, double glazing. These indicators were combined to a score, ranked and assigned to deciles. The mortality attributable to housing inequality was calculated as the difference between the observed and expected deaths. The expected deaths were computed by applying mortality in the least deprived decile to other deciles, stratified by 5-year age group, sex, and time. Results: Our results show that 20% of all deaths, equating to 2 564 289 deaths, occurring between 1991-2015 can be attributable to inequalities in housing. The proportion of deaths attributable to inequality in housing increased over time and was higher for men (26%) than for women (14%). The difference in age-standardized mortality rates between the most and the least deprived groups increased over time from 31 to 37% and from 10 to 26% for men and women, respectively. Conclusions: Housing conditions play an important role in mortality inequalities and ensuring good housing conditions is necessary for reducing inequalities. Key messages: Poor housing condition is associated with increased mortality. Our results show that 20% of all deaths, equating to 2 564 289 deaths, occurring between 1991-2015 can be attributable to inequalities in housing.